International Competition and Exchange Rate Shocks: A Cross-Country Industry Analysis of Stock Returns - Griffin, John M.; Stulz, René M. (Review of Financial Studies, 2001)
This article systematically examines the importance of exchange rate movements and industry competition for stock returns. Common shocks to industries across countries are more important than competitive shocks due to changes in exchange rates. Weekly exchange rate shocks explain almost nothing of the relative performance of industries. Using returns measured over longer horizons, the importance of exchange rate shocks increases slightly and the importance of industry common shocks increases more substantially. Both industry and exchange rate shocks are more important for industries that produce internationally traded goods, but the importance of these shocks is economically small for these industries as well.